Reused disposable ureteroscopes in retrograde intrarenal surgery: A new concept arises? - Horacio Sanguinetti; Juan Guillermo Ruiz; Maximiliano Lopez Silva; Norberto Bernardo (Indian Journal of Urology, 2025)
Introduction: Retrograde intrarenal surgery (RIRS) for renal lithiasis is widely used, with single-use ureteroscopes offering an excellent option. However, their high cost poses a challenge, prompting consideration of reusing disposable instruments. This study aims to compare stone-free rates (SFR) and complications between reprocessed disposable ureteroscopes and new ones in a multicenter cohort. Methods: This prospective, observational, multicenter study included patients who underwent RIRS between May 2022 and May 2023 at three centers in Argentina. Patients were divided into two groups: Group 1 used a brand new disposable ureteroscope and Group 2 used a reprocessed disposable ureteroscope. Stone size, location, stone-free rate, postoperative complications, and subjective evaluations of deflection and vision were analyzed. Results: Seventy-seven patients were included: 21 in Group 1 and 56 in Group 2. The average stone size was 10.9 mm in Group 1 and 8.6 mm in Group 2 (P = 0.0188). Stone location in the renal pelvis was 42% in Group 1 and 25% in Group 2 (P = 0.406). SFR were 71.4% in Group 1 and 73.2% in Group 2 (P = 0.999). No differences were found regarding the subjective assessment of vision and deflection as evaluated by the surgeons. Postoperative urinary tract infections occurred in 9.5% of Group 1 and 16% of Group 2 (P = 0.717). Conclusions: Despite the larger stone size in Group 1, the stone-free rate and postoperative infection rates were similar between both groups. Reprocessing disposable instruments does not appear to affect the effectiveness or infection rate of RIRS.